Epidemiology, pathophysiology, and pathogenesis of cryptorchidism. Evaluation and treatment of undescended testicle - Toliczenko-Bernatowicz, Dorota; Matuszczak, Ewa; Komarowska, Marta; Hermanowicz, Adam; Dębek, Wojciech (Pediatria Polska - Polish Journal of Paediatrics, 2020)
Cryptorchidism – the absence of one or both testes in the normal scrotal position – is the most common birth defect of the male genitalia. In full-term newborn boys its incidence is estimated at 2–5%. During the first three months of life, in half of these boys the testicles will descend spontaneously into the scrotum, but at the end of the first year of life 1% of boys will have cryptorchidism. Among boys born prematurely, about 30% of them have undescended testicles at birth, but also in such cases approximately 80% of undescended testes descend by the third month of life. The authors discuss the epidemiology, pathophysiology, aetiology, and treatment of undescended testicle in boys.